The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s13006-021-00436-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of hsa-miR-148a-3p and hsa-miR-125b-5p in human breast milk and infant formulae

Abstract: Background Milk-derived microRNAs (miRNAs), including hsa-miR-148a-3p (miR-148a) and hsa-miR-125b-5p (miR-125b), have been shown to be beneficial to the gastrointestinal function in infants. Here, we investigated their expression during lactation in humans and determined whether the infant formulae available in Japan contain these miRNAs. Methods Healthy Japanese women (n = 16) who gave birth vaginally or by cesarean section at the Teine Keijinkai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
2
13
0
5
Order By: Relevance
“…RNAs, on the other hand, are known to be unstable in harsh environments [ 220 , 221 ]. However, HBM-derived miRNAs remain remarkably stable even when treated with RNase in vitro [ 222 ]. Given that milk miRNAs are surrounded by a lipid bi-layered membrane and are supplied with adherence molecules, it has been proposed that their packaging in “vehicle” structures, such as exosomes, somatic cells and other microvesicles, may be vital for their long-distance passage [ 49 , 188 , 223 ].…”
Section: Circulating Mirnas In Hbmmentioning
confidence: 99%
“…RNAs, on the other hand, are known to be unstable in harsh environments [ 220 , 221 ]. However, HBM-derived miRNAs remain remarkably stable even when treated with RNase in vitro [ 222 ]. Given that milk miRNAs are surrounded by a lipid bi-layered membrane and are supplied with adherence molecules, it has been proposed that their packaging in “vehicle” structures, such as exosomes, somatic cells and other microvesicles, may be vital for their long-distance passage [ 49 , 188 , 223 ].…”
Section: Circulating Mirnas In Hbmmentioning
confidence: 99%
“…The upregulation of hsa-miR-342-3p in leprosy skin lesions has been described [ 69 ], but there is no evidence that it is related to atopic diseases. Regarding has-miR-148a-3p, we found that this miRNA is highly expressed in human breast milk, especially in the first days of breastfeeding, but there is no direct evidence linking it to atopic diseases [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Golan-Gerstl et al compared the composition and related functions of miRNAs between breast milk and infant formula EVs, finding that the known advantageous miRNAs highly conserved in mammalian milk EVs were not detected in several chosen infant formulas. Similarly, Chiba et al revealed that the levels of miR-148a and miR-125b highly expressed in human breast milk were significantly lowered in infant formulas, and Leiferman et al showed that only minimal concentrations of bovine milk miRNAs and no functional milk exosomes were detected in infant formula. This may partially explain the argument that infants fed with breast milk show stronger immunity than those fed with formula milk .…”
Section: Immunological Regulation In Infantsmentioning
confidence: 99%